2021
DOI: 10.1002/aur.2521
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on stress, anxiety, and coping in youth with and without autism and their parents

Abstract: In the wake of COVID‐19, the world has become a more uncertain environment—a breeding ground for stress and anxiety, especially for individuals with autism spectrum disorder (ASD). The study examined stress, anxiety, and coping in a data‐driven, real‐time assessment of 122 youth with and without ASD and their parents at the height of the COVID‐19 shutdown and three‐months later. Standardized measures were administered to ascertain stress and coping explicitly related to the pandemic (RSQ COVID‐19‐Child [self‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
30

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 66 publications
(97 reference statements)
4
70
0
30
Order By: Relevance
“…Hence, they might be extra reliant on their parents. The result is in line with the previous findings where the anxiety levels of parents were significantly correlated with children's ASC symptoms and behavioral problems during the pandemic (13,60).…”
Section: Relationships Among Variables Mid-lockdownsupporting
confidence: 92%
“…Hence, they might be extra reliant on their parents. The result is in line with the previous findings where the anxiety levels of parents were significantly correlated with children's ASC symptoms and behavioral problems during the pandemic (13,60).…”
Section: Relationships Among Variables Mid-lockdownsupporting
confidence: 92%
“…As in previous studies where many parents of autistic children reported an increase of stress and anxiety during the pandemic (Adams et al, 2021;Alhuzimi, 2021;Calvano et al, 2021;Corbett et al, 2021;Spinelli et al, 2020), almost all our sample of parents considered this period to be a highly stressful time to varying level. A general consensus emerged among the parents on the importance of having access to information to understand their autistic child's characteristics and to put in place measures suited to these characteristics.…”
Section: Supporting Autistic Children and Their Parentssupporting
confidence: 51%
“…Indeed, international studies are accumulating to support these fears. Parents of children with autism report wide-ranging adverse outcomes including increasing sleep issues [16], less physical activity [17], disruptive and restrictive behavior, and signs of regression in younger children [18], higher levels of irritability, behavioral problems, stress, and anxiety along with less adaptive coping strategies in school-aged children [19,20]especially for children with pre-pandemic behavioral and psychological issues [21].…”
Section: Introductionmentioning
confidence: 99%